Thermal analysis of composite beam structure based on a variable separation method for any volume heat source locations and temporal variations. (15th November 2022) - Ibouroi, L. Aboudou; Vidal, P.; Gallimard, L.; Ranc, I.
Abstract: This paper deals with an efficient method to compute thermal solutions with arbitrary heat source location and temporal variation for composite beams. For that, the associated Green's function is first computed. It is approximated as a sum of products of five separated 1D functions (depending on spatial coordinates x and z, the time t and impulse heat source locations x s and z s ). A dedicated iterative algorithm is proposed to control the computations of these five 1D functions. A regularized procedure has also to be carried out. Once the Green's function is computed, the temperature field can be deduced easily by computing 1D integrals for any heat source configurations. This interesting feature could be used in an iterative process such as identification problems. The present approach is assessed with different composite beam configurations submitted to various heat sources. Reference solutions issued from a finite element software are provided for comparison purpose.